2008
DOI: 10.1093/rheumatology/ken409
|View full text |Cite
|
Sign up to set email alerts
|

MEFV mutations in systemic onset juvenile idiopathic arthritis

Abstract: SoJIA patients had a significantly higher frequency of MEFV mutations but clinical studies with large number of patients are needed to confirm the association of MEFV mutations with SoJIA and its course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 13 publications
1
49
0
5
Order By: Relevance
“…Other inflammatory diseases including IBD accompany FMF with a gradually increasing frequency. In addition, the frequency of other inflammatory diseases (including juvenile rheumatoid arthritis) increases in conditions where IBD accompanies FMF (10)(11)(12). The fact that MEFV gene mutations are found with an increasing frequency in these inflammatory diseases supports this (13).…”
Section: Introductionmentioning
confidence: 87%
“…Other inflammatory diseases including IBD accompany FMF with a gradually increasing frequency. In addition, the frequency of other inflammatory diseases (including juvenile rheumatoid arthritis) increases in conditions where IBD accompanies FMF (10)(11)(12). The fact that MEFV gene mutations are found with an increasing frequency in these inflammatory diseases supports this (13).…”
Section: Introductionmentioning
confidence: 87%
“…Основанием для этого стало наличие общих клинико-лабораторных проявлений СЮА и ряда моногенных АВЗ, особенно CAPS, и вполне обоснованным явилось предположение, что у ряда пациен-тов под маской СЮА скрываются эти заболевания. Осуще-ствлялись попытки выявления каких-либо мутаций у паци-ентов с СЮА, они представлены в отдельных зарубежных публикациях, а в России пока эксклюзивны [12][13][14]. Экс-пертами в области изучения АВЗ для их идентификации предложены алгоритмы диагностики, включающие клини-ческие классификационные критерии, рекомендации по лечению [15][16][17][18][19].…”
Section: с о в P E м е н н а я р е в м а т о л о г и я № 3 ' 1 7 о р unclassified
“…Генетического подтверждения эта идея пока не нашла. Тем не менее в ряде работ показано, например, что у боль-ных СЮА, обнаруживались мутации в гене MEFV, ответст-венном за развитие семейной средиземноморской лихорад-ки (FMF) [12,13]. Исследования мутаций в генах NLRP3, TNFRSF1A, MVK у больных СЮА пока единичны [12][13][14].…”
Section: п о л и м о р ф и з м ы в ы я в л е н н ы е у п а ц и е н unclassified
“…Shimizu et al [3] first reported the heterozygous mutation of the Mediterranean fever (MEFV) gene in an adolescent with CRMO and only then began treatment with colchicine. The presence of this mutation is also highly prevalent in Henoch-Schönlein purpura (HSP), [4] Behçet's disease (BD), [5] ankylosing spondylitis (AS), [6] systemic onset juvenile idiopathic arthritis (SoJIA), [7] and even in fibromyalgia. [8] However, in cases involving these conditions, the clinical significance of this association is unknown, and studies with a larger sample size need to be conducted.…”
Section: Author's Replymentioning
confidence: 99%